2015
DOI: 10.15761/jsin.1000103
|View full text |Cite
|
Sign up to set email alerts
|

Growth and evolution of category fluency network graphs

Abstract: Background: Category fluency is a sensitive measure of cognitive integrity and is known to involve both frontal and temporal cortical areas. Network graph analysis is a technique used to analyze relationships between nodes and edges and calculate metrics such as path lengths between nodes and clustering coefficients.Objectives: To investigate network growth and preferential attachment in a network model of category fluency.Method: Category fluency results ("animals" recorded over 60 seconds) from subjects (N=3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The results from that initial study (Lerner et al, 2009) showed that the number of nodes decreased from normal to mild cognitive impairment to AD, as did the edges, and measures of complexity such as clustering coefficient and mean shortest path length also changed consistently between the groups. Further analysis using this method of graph construction showed that this method produced scale-free networks with small-world properties, thereby providing validation for the methodology (Lenio et al, 2016;Lerner et al, 2009;Shrestha et al, 2015).…”
Section: Simple Associationmentioning
confidence: 86%
See 2 more Smart Citations
“…The results from that initial study (Lerner et al, 2009) showed that the number of nodes decreased from normal to mild cognitive impairment to AD, as did the edges, and measures of complexity such as clustering coefficient and mean shortest path length also changed consistently between the groups. Further analysis using this method of graph construction showed that this method produced scale-free networks with small-world properties, thereby providing validation for the methodology (Lenio et al, 2016;Lerner et al, 2009;Shrestha et al, 2015).…”
Section: Simple Associationmentioning
confidence: 86%
“…It is clear from our previous work and the results presented here that group size is an important variable. Using subsets from a study of ∼350 individuals, Shrestha et al (2015) modeled network growth and demonstrated the emergence and change of network parameters with group size. Although our cohort was relatively small, comparisons with Shrestha and colleagues (2015) indicate that network parameters are relatively stable and that our group size appears acceptable for the initial analysis presented here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the nodes and edges of each learner are aggregated in a LAG by simply grouping all together. See also Lerner et al ( 2009 ), Shrestha et al ( 2015 ), Lenio et al ( 2016 ) for a similar methodology of graph construction by simple association. Sinha et al ( 2023 ) believe that if scale-free networks with small-world properties are produced with this method, then it is a valid method for graph construction.…”
Section: Vocabulary Production and Lexical Availability In Efl As A F...mentioning
confidence: 99%
“…This threshold is the only parameter in the SemNeT package's implementation of the Naïve Random Walk method and it defaults to 3. The Naïve Random Walk has demonstrated validity by finding exponential growth in the evolution of verbal fluency networks (Shreestha et al, 2015) as well as differences in semantic structure of people with mild cognitive impairments (Lerner et al, 2009).…”
Section: Naïve Random Walkmentioning
confidence: 99%